问题 解答题
下列各题怎样算简便就怎样算.
1
6
+
3
4
×
2
3
÷2
[1-(
1
2
+
3
8
)]÷
1
4
3
4
+
1
2
-
7
12
)×24
[4-(
3
4
-
3
8
)]×
4
29
17
24
×
3
4
+
17
24
÷4
2-
6
13
÷
9
26
-
2
3
答案

1
6
+
3
4
×
2
3
÷2

=

1
6
+
3
4
×
2
3
×
1
2

=

1
6
+
1
4
=
5
12

[4-(

3
4
-
3
8
)]×
4
29

=[4-

3
8
4
29

=

29
8
×
4
29

=

1
2

[1-(

1
2
+
3
8
)]÷
1
4

=[1-

7
8
]×4

=

1
8
×4

=

1
2

17
24
×
3
4
+
17
24
÷4

=

17
24
×(
3
4
+
1
4

=

17
24
×1

=

17
24

3
4
+
1
2
-
7
12
)×24

=

3
4
×24+
1
2
×24-
7
12
×24

=18+12-14

=16;

2-

6
13
÷
9
26
-
2
3

=2-

6
13
×
26
9
-
2
3

=2-1

1
3
-
2
3

=0;

多项选择题
问答题 简答题